CRITICAL DISCOURSE ANALYSIS “US CALLS CHINA, RUSSIA, IRAN, N. KOREA 'MORALLY REPREHENSIBLE' ON RIGHTS” THE JAKARTA GLOBE (APPLYING THE VAN DIJK THEORY IN MASS MEDIA) - Nurlaila Sari Harahap; Syahron Syahron; Dhara Ayu Paramitha; Muhammad Ali Sakti Nasution; Khairani Wahidah; Ridzky Hidayani; Felicia Bernadeth Simanjuntak (Proceedings of ISELT FBS Universitas Negeri Padang, 2018)
The formulation of this research problem is how to analyze the daily Jakarta Globe "Us Calls China, Russia, Iran, N. Korea 'Morally Reprehensible' on Rights" by applying Van Dijk model in Critical Discourse Analysis.This research aims to describe the critical discourse analysis van Dijk model constructed by Lesley Wroughton and David Brunnstrom as the news writers on April 22, 2018 at the official The Jakarta Globe. The theory used is van Dijk critical discourse analysis model. The result and discussion of this research indicate that (1) the macro structure contained in the discourse, namely human rights abuses (2) the superstructure, the introduction is opened by US labeling China, Russia, Iran and Korea as "morally reprehensible" on rights countries and highlighted by the arguments of US Deputy Secretary of State, John J. Sullivan and US relations with those countries (3) the microstructure, in semantic analysis, the negative statements used by the US to criticize China, Russia, Iran and Korea. In terms of syntax, the conjunction ‘and’ and ‘that’ dominate the content of this news to connect each clauses. In Stylistics, choice of negative words is used. From the rhetorical point of view, the size and type of letters indicate that human rights abuses are focussed.